A Community of Learning - Geriann Marie Walker (Journal of Research in Rural Education, 1993)
Elmira High School serves thesmall townofVeneta (3,300), theadjacent unincorporated community of Elmira 0,5(0) andtheoutlyingcommunities ofNoti (400) and Walton (300), total population 5,500. Veneta-Elmira is 15 miles from Eugene-Springfield, ametropolitan area ofabout 175,000. Eugene ishome totheUniversityofOregon andmajorindustries, and isseparated from Veneta-Elmira byawildlife refuge anda large reservoir.